(untitled) (Advancements in Homeopathic Research, 2022)
Ethics, an essential dimension of human research, is considered both as discipline and practice. For clinical research, ethically justified criteria for the design, conduct, and review of clinical investigation can be identified by obligations to both the researcher and human subject. Informed consent, confidentiality, privacy, privileged communication, and respect and responsibility are key elements of ethics in research.